Lucifer. The sixth and final season [videorecording (DVD)] - Kapinos, Tom (SDS : Warner, 2022)
In the sixth and final season of Lucifer, we close the chapter on our crime-solving Devil. With Los Angeles no longer the battleground for his angelic siblings, Lucifer's relationship with Chloe has never been stronger. Life is good. But if we know anything about this fallen angel, it's that his past always finds a way of catching up to him.